Business ethics and corporate sustainability - Tencati, Antonio; Perrini, Francesco (Studies in transatlantic business ethics, 2011)
This authoritative book includes cutting-edge insights from leading European and North American scholars who reflect upon business ethics' foundations, firms, markets and stakeholders in order to design more sustainable patterns of development for business and society. Together, the contributing authors advance critical, innovative and imaginative perspectives to rethink the mainstream models and address the sustainability challenge.